Bioactive Compounds from Microalgae Spirulina platensis as Antibacterial Candidates Against Pathogen Bacteria - Noor Hidhayati; Ni Wayan Sri Agustini; Marsiti Apriastini; Dhea Peby Ananda Diaudin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Microbial infection by bacteria has caused severe health problems worldwide. Treatment with antibiotics as the current solution has several drawbacks and triggers the phenomenon of bacterial resistance. Therefore, there is an urgency to look for a natural antimicrobial that is safer and has fewer side effects. One of the most promising antibacterial agents is Spirulina platensis. This research was conducted to evaluate the antibacterial activity of microalgae S. platensis against Propionibacterium acne, Staphylococcus epidermidis, and Enterobacter aerogenes and identify compounds from the active fraction of microalgae. Biomass was extracted with ethanol 96% using the reflux method then partitioned with immiscible solvents such as hexane, ethyl acetate, and water. Partial purification was carried out by chromatography techniques such as thin-layer chromatography and column chromatography. The compounds of active fractions were identified by GC-MS analysis. The result showed that ethyl acetate extract had vigorous antibacterial activity against all tested bacteria. The highest activity (14.4 ± 0.63 mm and 16.9 ± 1.48 mm) was achieved against P. acne; followed by S. epidermidis (13.05± 0.14 mm and 13.15 ± 0.0 mm), and E. aerogenes (11.7 ± 2.05 mm and 12.6 ± 1.90 mm), at concentrations 20,000 ppm and 30,000 ppm, respectively. The results indicated that the extract is more sensitive to Gram-positive bacteria (P. acne and S. epidermidis) than Gram-negative bacteria (E. aerogenes). Purification of the extract resulted in fraction 2 and fraction 6 as the most potential fractions for further analysis and identification. Based on the antibacterial activity, inhibition zones of fractions are wider than extracts. It could be assumed that the purification process enhances the activity of a sample. GC-MS analysis revealed that the dominant compounds of fractions 2 and 6 were bis (2-ethylhexyl) phthalate (67.76%) and 1,2-Benzendicarboxilic acid, bis (2-ethylhexyl) ester (50,88%), respectively. This result indicated that the ethyl acetate fraction of the microalgae S. platensis has the potential as a natural antibacterial.